Public costs attributable to obesity: sample from the USF Itamarati, Patos de Minas (Research, Society and Development, 2021)
Introduction: The higher the body mass index (BMI) of a patient, the greater the risk of the patient developing obesity-related diseases. Likewise, the severity of obesity and related diseases increases as BMI increases. Objective: to assess the costs of obesity and related diseases in Brazil from the perspective of society and health systems, in view of the analysis of estimated costs attributable to this main pathology, considering the costs of outpatient procedures, medicines distributed by the SUS to treat the disease and request of exam. Methodology: analytical observational approach developed at the Itamarati Basic Health Unit, located in the Jardim Itamarati neighborhood, in the city of Patos de Minas, Minas Gerais, using data from the Viver Platform, physical records and DATASUS. Results and discussion: given the results of this study and others cited here, it is noted that, considering obesity as a risk factor for hypertension and diabetes separately, the costs attributable to this disease are high, and the estimates of costs attributable to the main diseases Chronic diseases associated with inadequate nutrition show the great economic burden of these diseases for the SUS. The data show the need to prioritize integrated and intersectoral policies for the prevention and control of hypertension, diabetes and obesity. Conclusion: Obesity imposes a high cost to the health of people and public administration. Thus, by understanding the pathophysiology of obesity, it will allow healthcare providers to better manage the set of diseases supported by this main pathology that affect an individual.